Assessment of the Investigative Objectivity in the Execution of Detention Authority under the Principle of Unity of Command in the Indonesian Military Criminal Justice System - Sulistiani, Lies; Rusmiati, Elis; Prasetyoandi, Destri (Journal of Ecohumanism, 2024)
The Indonesian National Army (TNI), as the Armed Forces in the country, operates under specific regulations to enforce military law, primarily governed by Law Number 31 of 1997 concerning Military Justice. According to Article 1 of the law, the responsibility for conducting investigations falls to Military Police Investigators, alongside Military Prosecutors and Superiors who have the right to punish suspects. Therefore, this research aimed to analyze the authority of Military Police Investigators within the investigativeprocess, with a specific focus on their power to detain suspects. Under the current provision, Military Police Investigators lacked the independent authority to detain, which might compromise the objectivity of investigations. A normative juridical method was adopted based on a literature review and secondary data. The results showed that Military Police Investigators did not have the authority to detain suspects without an order from a Superior who has the right to punish, as stipulated in Law Number 31 of 1997 concerning Military Justice. For the investigation to run more objectively, Military Police Investigators needed to be granted the authority to detain suspects independently, without requiring prior authorization from a superior.